Ethiopian English Language Teachers' Perceptions of Their Profession and Job Satisfaction - Gezahegn, Girma (Universitas Jambi, Magister Program of English Education Department, 2025)
This study investigated Ethiopian English teachers' perceptions of their profession and job satisfaction using surveys and interviews. While teachers reported finding significant meaning and pride in their work, a prevalent theme was the perception that the teaching profession is largely undervalued within society. Major factors contributing to potential attrition included low pay, inadequate leadership, and heavy workloads. Conversely, positive aspects identified were strong collegial support and a sense of professional fulfilment derived from teaching. The findings suggest that despite some intrinsic rewards, systemic challenges negatively impact morale and retention. The study concludes by advocating for comprehensive, systemic reforms aimed at increasing job satisfaction, improving teacher retention rates, and elevating the societal respect accorded to the teaching profession.